Prevalence and antimicrobial resistance profiles of extended-spectrum beta-lactamase-producing Escherichia coli in East Tennessee dairy farms - Gelalcha, Benti D.; Gelgie, Aga E.; Kerro Dego, Oudessa (Frontiers in Veterinary Science, 2023)
Introduction The extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae, such as Escherichia coli, are emerging as a serious threat to global health due to their rapid spread and their multidrug-resistant (MDR) phenotypes. However, limited information is available regarding the prevalence and antimicrobial resistance (AMR) profile of ESBL-E. coli in the United States dairy farms. This study aimed to determine the prevalence and AMR pattern of ESBL-E. coli in East Tennessee dairy cattle farms. Methods Rectal fecal samples from dairy cattle (n = 508) and manure (n = 30), water (n = 19), and feed samples (n = 15) were collected from 14 farms. The presumptive E. coli was isolated on CHROMagar™ ESBL and confirmed by matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS). Antimicrobial susceptibility testing was performed on the ESBL-E. coli isolates. Results and discussion From 572 fecal and farm environmental samples, a total of 233 (41%, n = 572) ESBL-E. coli were identified. The prevalence of fecal ESBL-E. coli was 47.5% (95% CI: 46.2–49.2). The within-farm prevalence of ESBL-E. coli ranged from 8 to 100%. Recent treatment history with third-generation cephalosporins (3GC), cow parity ≥3, and calves were the independent risk factors associated (P < 0.05) with fecal carriage of ESBL-E. coli. Overall, 99.6% (n = 231) ESBL-E. coli tested were phenotypically resistant to at least one of the 14 antimicrobial agents tested. The most common AMR phenotypes were against beta-lactam antibiotics, ampicillin (99.1%; n = 231 isolates), and ceftriaxone (98.7%, n = 231). Most ESBL-E. coli isolates (94.4%) were MDR (resistance to ≥3 antimicrobial classes), of which 42.6% showed co-resistance to at least six classes of antimicrobials. ESBL-E. coli isolates with concurrent resistance to ceftriaxone, ampicillin, streptomycin, tetracycline, sulfisoxazole, and chloramphenicol are widespread and detected in all the farms. The detection of MDR ESBL-E. coli suggests that dairy cattle can be a reservoir for these bacteria, highlighting the associated public health risk.